A SURVEY OF DRUGS UTILIZED IN PRIMARY POST PARTUM HAEMORRHAGE AT A TERTIORY CARE TEACHING HOSPITAL (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction: The most common type of obstetric hemorrhage is postpartum haemorrhage (PPH), mainly primary PPH. Primary PPH is defined according to WHO as blood loss of 500 ml in the first 24 h postpartum. Definitions vary in various parts of world and are often based on estimation of blood loss. It can also be defined as fall in haematocrit >10%. Major cause of avoidable visits to emergency room and hospitalizations at the time of very. Materials and Methods: It is Prospective, Observational study, approximately 115 prescription analyzed. Written informed consent was taken from the eligible patients included in the study. Drugs data collected by reviewing the prescriptions prescribed . Data of all the 115 patients enter in Microsoft excel 2007 and analysed by using SPSS version 20.0 Software. Prescription pattern was evaluated by using WHO core drug prescribing indicators and US-FDA Drug Risk.RESULTS : Among 115, only 34 (29.5%) patients had antenatal check-ups at least 3 visits while rest 81 (70.43%) were not booked. Maximum cases were between age group of 21-25 Which contribute to 57 (49.56%). Among 115 cases, 19 patients had medical disorders, among them most Common was hypertension which contribute to 10 cases (43.47%) followed by sickle cell disease 7 (30.43%).Only 3(13.04%) suffered from diabetes and cardiac diseases. Conclusion: Our study concludes that visual estimation of postpartum blood loss is an inaccurate method to determine the amount of blood loss in PPH, resulting in underestimation and misdiagnosis of PPH. Multigravidas have been found to have higher incidence of PPH. Regular antenatal check-ups and improvement obstetric education are mandatory to decrease the incidences of PPH. Apart from mechanical measures and oxytocin alone, some other Uterotonics drugs were needed to control the PPH, in patients with inadequate antenatal car .
Keywords: Primary postpartum haemorrhage; Uterotonic drugs; Survey of drugs